The effectiveness of using LEGO® robotics kits as cognitive and social rehabilitative toys. (28th February 2020) - Caci, Barbara
The present article offers a theoretical contribution to the understanding of the effectiveness of using robotics as cognitive and social rehabilitative toys. Starting from the theoretical foundations of educational robotics in the framework of constructionism, it provides methodological indications related to game activities with robotics behaviour construction kits, such as LEGO® Ev3. Moreover, it discusses empirical studies that evaluated the effectiveness of the use of robotics behaviour construction kits in the field of intellectual disabilities. Practical implications of the present study might be useful for educators, school psychologists, or rehabilitative therapists in the field of special educational needs.